Liquid Biopsy in Cancer Patients The Hand Lens for Tumor Evolution - Russo, Antonio; Giordano, Antonio; Rolfo, Christian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana Press, 2017)
This text is designed to provide readers with a useful and comprehensive resource and state-of-the-art overview about the new, growing and fast-expanding field of (3z(Bliquid biopsy(3y (Bfor the management of cancer patients. The liquid biopsy represents an important turning point in oncology since it provides a tool for a serial monitoring of disease. Liquid biopsy is our (3z(Bhand lens(3y (Bto follow molecular changes that characterize tumor development and progression. The book provide a unique and valuable resource on the clinical relevance of liquid biopsy as well as on the technical aspects of liquid biopsy analysis. All invited authors are recognized experts in their field. Liquid Biopsy in Cancer Patients: The Hand Lens for Tumor Evolution is targeted to resident and fellows physicians, medical oncologists, molecular biologists and biotechnologists.s
Introduction -- Precision Medicine: Are We There? -- Clonal Cancer Evolution and Intra-tumor Heterogeneity -- Tissue vs. Liquid Biopsy: Opposite or Complementary? -- Technical Aspects for the Evaluation of Circulating Tumor Cells (CTCs) -- Technical Aspects for the Evaluation of Circulating Nucleic Acids (CNA): Circulating Tumor DNA (ctDNA) and Circulating MicroRNAs -- Technical Aspects for the Evaluation of Exosome and their Content -- Liquid Biopsy in Breast Cancer -- Liquid Biopsy in Head and Neck Cancers -- Liquid Biopsy in NSCLC -- Liquid Biopsy in Gastric Cancer -- Liquid Biopsy in Pancreatic Cancer -- Liquid Biopsy in HCC -- Liquid Biopsy in CRC -- Liquid Biopsy in GIST -- Liquid Biopsy in Kidney Cancer -- Liquid Biopsy in Melanoma.
Keywords: Medicine; Oncology; Pathology; Medicine & Public Health; Pathology; Oncology